Ultrasensitive Multilayer MoS2‐Based Photodetector with Permanently Grounded Gate Effect. (13th February 2020) - Naqi, Muhammad; Kaniselvan, Manasa; Choo, Sooho; Han, Gyuchull; Kang, Sangjin; Kim, Jeonghun; Yoon, Youngki; Kim, Sunkook
Abstract: 2D materials, specifically MoS2 semiconductors, have received tremendous attention for photo‐sensing applications due to their tunable bandgap and low noise levels. A unique photodetector using multilayer MoS2 as the semiconductor channel, in which the gate electrode of the device is permanently connected to the grounded source electrode to introduce rectification, is reported. The proposed grounded‐gate photodiode exhibits high photoresponsivity of 1.031 A W −1, excellent photodetectivity (>6 × 10 10 jones), and highly stable rise/fall time response (100–200 ms) under illumination of visible light (at the wavelengths of 405, 532, and 638 nm). Numerical device simulations using quantum transport methods and photoconductive effects are used to explain the device operation. It is also suggested that the gate metal work function can be carefully chosen to increase the sensitivity of the grounded‐gate photodetector by suppressing the dark current. The grounded‐gate device proposed, owing to the properties of rectifying behavior, low contact resistance, consistent photoresponsivity, and linear sensitivity, provides a new platform for next‐generation applications in the field of electronics and optoelectronics. Abstract : A unique photodetector using multilayer MoS2 as the semiconductor channel, in which the gate electrode is permanently connected to the grounded source electrode to introduce rectification, is reported. The proposed grounded‐gate photodiode exhibits high photoresponsivity (1.031 A W −1 ), excellent photodetectivity (>6 × 10 10 jones), and highly stable rise/ fall time response (100–200 ms) under illumination of visible lights.